The Impact of Workplace Counselling on Employee Performance - Motsomotso, Maletlatso (Indonesian Journal of Advanced Research, 2025)
Organizations take care of their employees through workplace counselling which enables them to effectively perform the duties assigned to them.  This paper aimed to examine the impact of workplace counselling on employee performance. 22 face-to-face semi-structured interviews were used to collect data in employees working in the ministry of transport.  The findings of this study indicate that workplace counselling affects employees through financial stability, reduced emotional disorders, increased work morale, ability to resolve issues and good communication/interaction with others.  The findings of this study add more knowledge on workplace counselling in the context of Lesotho.  Therefore, future studies may focus on other districts, to get more insights on the issue of workplace counselling and employee performance.